PENGARUH KIT-IPA TERHADAP HASIL BELAJAR IPA DALAM PEMBELAJARAN TEMATIK SISWA KELAS V MIN 3 PONTIANAK - Awalina, Chintiya; Marli, Suhardi; Uliyanti, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe problem in this research was â€œHow does the effect of KIT-IPA toward the learning outcomes of science in thematic learning of fifth grade student of Madrasah Ibtidaiyah Negeri 3 Pontianak?â€. The model used in this study was an experimental method to form the study was Quasi Experimental Design, with experimental design Nonequivalent Control Group Design. The sampling technique used non probability sampling with purposive sampling type. Data collection tools used in the form of learning outcomes document and of a written objective-shaped test with 45 questions. Based on statistical calculations of theÂ  final test experimental class average of 75,68 and learning results of final test control class 67,64, the final test data was obtained at 2,940 and (Î± = 5% and dk 34 + 35 â€“ 2 = 67) amounting to 1,669, because (2,940)>(1,669), then Ha is received. This means that the use KIT-IPA in thematic learning has a moderate influence on the learning outcomes of fifth grade student of Madrasah Ibtidaiyah Negeri 3 Pontianak.Â Keywords: Learning Outcomes, KIT-IPA, Thematic Learning